Physico-Chemical Analysis of Protein Fortified Papaya Jam - Dimas Bayu Pinandoyo; Saleem Siddiqui; M.K. Garg (Universitas Al Azhar Indonesia, 2019)
Abstract - Vegetarian food products content less protein source compare to non-vegetarian. Protein fortification is one of the option can be chosen to fulfil protein needs of the vegetarian consumer. Papaya Jam was fortified with protein isolate from soy bean with amount of 5%. The analysis of physico-chemical analysis was done using Association of Official Agricultural Chemist (AOAC) official methods of analysis. The physico-chemical analysis of protein fortified papaya jam showed that the product had 31.07± 0.20 % moisture contents, 68.00 ± 0.54 % Total Soluble Solid, 0.49 ± 0.02 % of acidity, 3.27± 0.52 in pH, 31.30± 0.10 mg/100g ascorbic acid content, 53.60 ± 0.18 % total sugar amount, 33.60± 0.78 % reducing sugar, 2.81± 0.08 mg/100 total carotenoid, 0.540.54 ± 0.02 mg/100g total phenol, and 5.43 ± 0.06 % dwb of crude protein content. The physico-chemical of protein fortified papaya jam found still in the range of jam standard standardized by FAO and previous research results for physico-chemical analysis of jam.ntuk naskah berbahasa Indonesia, abstrak ditulis dalam bahasa Indonesia dan bahasa Inggris.Keywords - Physico-chemical, protein, fortification, papaya, jam